2013
DOI: 10.4161/rna.25273
|View full text |Cite
|
Sign up to set email alerts
|

PPR proteins shed a new light on RNase P biology

Abstract: A fast growing number of studies identify pentatricopeptide repeat (PPR) proteins as major players in gene expression processes. Among them, a subset of PPR proteins called PRORP possesses RNase P activity in several eukaryotes, both in nuclei and organelles. RNase P is the endonucleolytic activity that removes 5′ leader sequences from tRNA precursors and is thus essential for translation. Before the characterization of PRORP, RNase P enzymes were thought to occur universally as ribonucleoproteins, although so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 90 publications
1
45
0
Order By: Relevance
“…The crystal structure of T. maritima RNase P in complex with tRNA showed that A112 and G147 in the S-domain in RNase P RNA were arranged adjacent to G19 and C56 in the D and TwC loops, respectively [6]. Previously, cross-linking and mutational analyses suggested that G19 and C56 in tRNA Phe are involved in the interaction with PRORP1 [15,16]. It was therefore proposed that PRORP1 recognizes pre-tRNA in a similar manner to bacterial RNase Ps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The crystal structure of T. maritima RNase P in complex with tRNA showed that A112 and G147 in the S-domain in RNase P RNA were arranged adjacent to G19 and C56 in the D and TwC loops, respectively [6]. Previously, cross-linking and mutational analyses suggested that G19 and C56 in tRNA Phe are involved in the interaction with PRORP1 [15,16]. It was therefore proposed that PRORP1 recognizes pre-tRNA in a similar manner to bacterial RNase Ps.…”
Section: Discussionmentioning
confidence: 99%
“…PRORP1 comprises five tandem pentatricopeptide repeat (PPR) motifs, a central linker domain, and a metallonuclease domain belonging to the NYN family [14]. Furthermore, cross-linking and mutational analyses suggested that G19 and C56 in tRNA are involved in the interaction with PRORP1 [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The phylogenetically conserved RNA component of RNase P is the catalytic moiety of the enzyme (Guerrier-Takada et al 1983;Chen and Pace 1997;Pannucci et al 1999;Thomas et al 2000;Kikovska et al 2007;). In a number of cases, the ribonucleoprotein RNase P is supplemented or altogether replaced by unrelated protein-only enzymes termed PRORPs (Pinker et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, this view was contradicted and the interest in RNase P renewed with the identification of a second type of RNase P in eukaryotes that was composed only of protein (Holzmann et al, 2008;Gobert et al, 2010;Pinker et al, 2013). This other type of RNase P, called PRORP for 'PROtein-only RNase P', was found in four out of five eukaryote supergroups, in organelles and/or in the nucleus (Lechner et al, 2015).…”
Section: Introductionmentioning
confidence: 99%